Farmer’s Perception Regarding Cultivation of Rice in Less Water in Tehsil Pindi Bhattian, District Hafizabad - Haider, Samsam; Abid, Syed Amir Zia; Saeed, Umair; Sadaf, Saima (PSM Biological Research, 2022)
Rice production in Pakistan needs to increase to feed the fast-growing population. Though a complete assessment of the level of water scarcity in Pakistani rice production is still lacking, there are signs that declining quality and availability of water resources are threatening the sustainability of the irrigated-based rice production system. The purpose of the study was to assess farmer’s perceptions regarding the cultivation of rice in less water in Tehsil Pindi Bhattian, District Hafizabad. A survey questionnaire was used as an instrument for assessing the desired research problem. Factors like demographic profiles of the respondents, constraints, their knowledge level, and satisfaction level were used to assess the research area. A systematic sample of 60 farmers was taken for analysis purposes. The results showed that almost all the farmers were not aware of the practices about rice cultivation in less water. The results revealed that no information is provided to the farmers and the extension field staff did not conduct the survey and there are no field assistants in the research area. It is very important to reduce the quantity of water which is used for the irrigation of rice crop. Because the water level below the earth is decreasing day by day and the soil is becoming saline and its productivity is reducing continuously. The extension field staff should provide information about the new varieties and the water management strategies for the cultivation of rice in less water at the doorstep of the farmer.